Misconceptions of earnings and their consequences for social stratification in vocational aspirations and attainment - Dräger, Joscha [Verfasser]; Wicht, Alexandra [Verfasser] (My University, 2021)
“This paper makes two contributions to the literature on social stratification in vocational attainment. First, we evaluate whether labour market literacy, as measured by knowledge about earnings in different occupations, is socially stratified. Second, we analyse whether differences in expected earnings between high-income and low-income occupations contribute to the social stratification in vocational aspirations and attainment using serial mediation based on data from the German National Educational Panel Study. We find that students are well informed about earnings, on average, but substantially underestimate earnings in some occupations. Students from low socio-economic status (SES) families underestimate earnings more than those from high SES families, particularly earnings in high-status occupations. Therefore, low SES students expect smaller earning differences between high-income and low-income occupations than high-SES students. In turn, small expected differences between high-income and low-income occupations are associated with lower vocational aspirations as well as attainments. Differences in expected earnings of high-income and low-income occupations mediate 4% of the differences in vocational aspirations by parental SES and 2% of the differences in vocational attainment.” (authors’ abstract; BIBB-Doku)
Keywords: G 1.2 Arbeitsmarkt; G 1.2.2 Beschäftigungs- und Arbeitsverhältnisse; S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; 370; 330; Schüler; Arbeitsmarkt; Einkommen; Erwartung; Fachwissen; Informationsverhalten; Bildungsaspirationen; Soziale Schichtung; Soziale Ungleichheit